2022
DOI: 10.3389/fnins.2022.835538
|View full text |Cite
|
Sign up to set email alerts
|

Not Only in Sensorimotor Network: Local and Distant Cerebral Inherent Activity of Chronic Ankle Instability—A Resting-State fMRI Study

Abstract: BackgroundIncreasing evidence has proved that chronic ankle instability (CAI) is highly related to the central nervous system (CNS). However, it is still unclear about the inherent cerebral activity among the CAI patients.PurposeTo investigate the differences of intrinsic functional cerebral activity between the CAI patients and healthy controls (HCs) and further explore its correlation with clinical measurement in CAI patients.Materials and MethodsA total of 25 CAI patients and 39 HCs were enrolled in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(62 reference statements)
1
8
0
Order By: Relevance
“…For example, if more coherence of the cerebellum is needed to stabilize the ankle when running than when resting, it might also be more challenging for patients with worse resting cerebellar coherence to meet the functional demand of running. Our findings on the correlation between the ReHo values and the self-reported feeling of instability intensity might also indicate its relationship with ankle instability, and the recent ReHo study on cerebral cortex also supported that the premotor cortex of the patients had to be more coherent to compensate for sensory deafferentation in ankle instability (15). For this mechanism, we tentatively surmise that the aforementioned joint deafferentation might influence cerebellar lobule VIIIb (reducing ReHo values), thereby causing a failure of appropriate motor output by cerebellar lobule VIIIb (presenting as functional instability).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For example, if more coherence of the cerebellum is needed to stabilize the ankle when running than when resting, it might also be more challenging for patients with worse resting cerebellar coherence to meet the functional demand of running. Our findings on the correlation between the ReHo values and the self-reported feeling of instability intensity might also indicate its relationship with ankle instability, and the recent ReHo study on cerebral cortex also supported that the premotor cortex of the patients had to be more coherent to compensate for sensory deafferentation in ankle instability (15). For this mechanism, we tentatively surmise that the aforementioned joint deafferentation might influence cerebellar lobule VIIIb (reducing ReHo values), thereby causing a failure of appropriate motor output by cerebellar lobule VIIIb (presenting as functional instability).…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to distant connectivity methods that explore the association between different regions, ReHo might be able to determine whether the cerebellum is a key region with abnormally organized neurons involved in ankle instability ( 13 , 14 ). Recently, Shen et al ( 15 ) also investigated the ReHo of patients with ankle instability, but only the cerebral cortex was studied, and the cerebellum was ignored. Because poor functional coherence was supposed to be maladaptive, we speculated that low cerebellar ReHo values could be observed in ankle instability, which might be a necessary addition to previous structural evidence to improve our understanding of maladaptive neuroplasticity in ankle instability ( 16 ).…”
mentioning
confidence: 99%
“…In addition, the ROC results indicated that the MFG, right MTG, cerebelum_6_L, and left lingual gyrus might have discrimination ability between groups. Similarly, increasing evidence suggests that structural and functional alterations in the MFG and MTG are associated with the mechanisms of chronic pain (Huang et al, 2020; Shen et al, 2022). Based on this information, we speculate that brain structural and functional differences may affect multiple dimensions of pain processing, including sensory, emotion, cognitive, and motor function, further revealing the complexity of the pathophysiological mechanisms of bone metastasis pain.…”
Section: Discussionmentioning
confidence: 99%
“…Significant alterations in the FC between the OFC and the pre/postcentral gyrus have been documented in individuals with chronic ankle instability (CAI) ( Shen et al, 2022 ). In the CAI population, a comparative analysis against the healthy control group reveals increased FC between the pre/postcentral gyrus, the sensorimotor network; while a concomitant decrease in FC is observed between the OFC and ACC, which associated with emotion or pain processing ( Shen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%